Human Flourishing in Cross Cultural Settings. Evidence From the United States, China, Sri Lanka, Cambodia, and Mexico - Wȩziak-Białowolska, Dorota; McNeely, Eileen; VanderWeele, Tyler J. (Frontiers in Psychology, 2019)
This paper investigates human flourishing in five culturally distinct populations. Empirical differences in human flourishing were examined using the recently proposed Flourish Index (FI) and Secure Flourish Index (SFI). Five domains for human flourishing are proposed for FI: (D1) happiness and life satisfaction; (D2) physical and mental health; (D3) meaning and purpose; (D4) character and virtue; and (D5) close social relationships. Specification of SFI was augmented by an additional financial and material stability domain (D6). Psychometric properties of FI and SFI were examined with data from the Health and Well-Being Survey. Between June 2017 and March 2018, a total of 6,373 respondents participated in the study – in the US (4083 participants), Sri Lanka (1284 participants), Cambodia (587 participants), China (419 participants) and Mexico (2500 participants). Exploratory and confirmatory factor models were used to validate the proposed indices. An exploratory approach informed analysis for item groupings. Confirmatory factor models were used to investigate the hierarchical structure of the indices. Configural, metric and scalar measurement invariance were established, which not only supported the universal character of the indices but also validated use of indices in culturally distinct populations. Findings from our study enrich our knowledge about human flourishing, providing unique comparative results for five populations. With the exception of happiness and life satisfaction, respondents in the US, despite enjoying the highest financial and material stability, scored the lowest in all other domains of human flourishing. Respondents in China excelled in close social relationship and health domains. In addition to life satisfaction and happiness, character and virtue were blooming in Cambodia. Respondents in Mexico, despite having the lowest scores in financial and material stability, had the greatest meaning and purpose to their lives. Respondents in Sri Lanka were the least happy and satisfied with life.